Demographic Factors on Cyberbullying and Victimisation among University Students - Vishwakarma, Babita; Kumari, Pushpa; Vishwakarma, Amit Kumar (Indian Journal of Extension Education, 2024)
As a result of technological advancements, communication methods have evolved, and in India, everyone uses various gadgets to access the Internet. Digital communication has transformed traditional bullying into cyberbullying. The study, conducted in 2023, aims to investigate the effects of gender, marital status, and family type on cyberbullying among university students. A sample of 150 university students, ages 16 to 27, was obtained from Banaras Hindu University, Varanasi. The study hypothesizes that gender, family types, and marital status have a significant impact on students cyberbullying because of variations in coping mechanisms and susceptibility to mental health issues. It is expected and verified that gender, family types, and marital status, which are divided into two categories, have a major impact on cyberbullying. Data analysis has used three-way ANOVA and other suitable statistical procedures to examine the impact of demographic factors on cyberbullying outcomes. The study presents novel findings on married men, indicating that they are more susceptible to cyberbullying than married women. The outcome, constraints, and future course to address the impact of cyberbullying and the variations in student gender, family structure, and marital status are also discussed and may be crucial inputs for future policy advocacy.
Keywords: Cyberbullying; Cyber victimisation; Perpetrators; Victims; Adolescents